Successful thoracoscopic excision of complex supracardiac middle mediastinal bronchogenic cyst in an infant - Amit Raut; Sushil Parakh; Akanksha Parakh; Neha Mukhi (Wolters Kluwer Medknow Publications, 2022)
Introduction: We report the first case of complex supracardiac middle mediastinal foregut duplication lesion compressing and adherent to the heart, managed successfully thoracoscopically in an infant, in an innovative way. Materials and Surgical Technique: A 1-year-old girl was diagnosed as having supracardiac middle mediastinal foregut duplication lesion. It was completely overlying and adherent to her heart giving transmitted pulsations to the lesion, causing indentation over the left atrium and surrounded by all vital structures such as aorta, pulmonary artery, bronchi and phrenic nerve. After proper counselling of parents and relatives, the patient was posted for surgery. After proper positioning, thoracoscopic access was gained, difficulty here was neither bulge nor surface marking of the lesion was seen in thoracic cavity anywhere, considering the anatomical relations. The mediastinal pleura was opened, through a very narrow window for accessing the lesion, which was surrounded by vital structures in the middle mediastinum. A gentle dissection of the lesion was done to relieve it from adjacent adhered thoracic vitals structures successfully. Histopathological examination confirmed it as a bronchogenic cyst. Discussion: Foregut duplication cyst, especially bronchogenic cysts, have been reported at various locations, however, supracardiac middle mediastinal bronchogenic cyst completely sitting on the heart, adherent to it causing compression of the left atrium and left bronchus and surrounded completely by the aorta, pulmonary artery and bronchus, has not been reported till date. Also, successful thoracoscopic excision of such rarely located lesion moving with heart, in a 1-year-old girl, has not been reported yet.